Perbandingan Efektivitas Digital Marketing Melalui Platform Instagram dan Tiktok Pada Ritel Makanan dan Minuman - Bhikuning, Dixian; Wasiati, Hera; Radinka, Ivanda Davin; Satria, Noval (Jurnal Ilmiah Global Education, 2025)
This research analyzes the comparative effectiveness of digital marketing through Instagram and TikTok platforms in the food and beverage retail sector using a quantitative survey-based approach involving 50 business owners. The research objective is to identify the strategic advantages of each platform based on three key indicators: Engagement Rate, Reach, and Conversion Rate. Descriptive analysis results demonstrate TikTok's superiority in Engagement Rate (8.7% vs 5.2%) and Conversion Rate (3.8% vs 2.1%), while Instagram excels in Reach (12,000 vs 9,500). Multiple linear regression analysis confirms the significant influence of all three indicators on digital marketing effectiveness, with Conversion Rate as the dominant predictor (β=0.41), followed by Engagement Rate (β=0.38) and Reach (β=0.29). The constructed model shows substantial predictive power (R²=0.72). The findings suggest differentiated marketing strategies based on each platform's unique characteristics, with TikTok optimized for interaction and conversion through interactive and trend-responsive content, while Instagram focused on maximizing reach through premium visual content and e-commerce integration. The implications of this research contribute to the development of a data-driven strategic framework for optimizing digital marketing resource allocation.